CAT SHELTER BANJARBARU - Nugraha, Akbar; Huzairin, Muhammad Deddy (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Caring for pets has become part of the lifestyle of modern society. The high interest in keeping animals is directly proportional to the growth of the abandoned animal population in Banjarbaru City. The follow-up to this problem is to create a shelter facility for abandoned animals who are sick, injured, tortured, or need protection in the form of Cat Shelters. The design of the Cat Shelter in Banjarbaru pays attention to the habits and character of cats. Programmatic architecture is used to organize space functions based on the flow of cat rescue activities and the interaction of cats and humans. The attractive concept is applied in the design to be able to make humans and cats whose characters are spoiled and cute have good interactions. The design was made several times to separate cat rescue activities and cat interaction activities